Assessing the Technical Feasibility and Resource Integration of Hybrid Offshore Wind and Tidal Stream Energy System (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The integration of tidal streams and offshore wind energy systems has obtained increasing attention as a promising approach to employing renewable energy resources. Tidal stream energy, derived from the kinetic energy of tidal currents, offers a predictable and stable power source, whereas offshore wind energy uses the abundant wind resources available at sea. To integrate both resources, parameters such as wake effects could be incorporated into a decision-making tool to identify suitable sites, enhance overall system performance, and increase energy generation. While the identification of suitable locations for development by assessing whether one or both types of energy are viable for remote areas has already been addressed, this research specifically aims to examine whether models that account for wake effects in the performance of offshore wind farms can also be applied to tidal stream systems.The proposed method looks to assess the wake characteristics driven by each turbine producing the same power output using the same model. To address this goal, tools such as FAST. Farm will help to assess relevant physics for predicting power performance, loads and velocity deficits. Fast.Farm uses the Dynamic Wake Meandering (DWM) model and low and high-fidelity tools to evaluate wind farm design and analysis. This investigation will provide insight into the applicability of these techniques for tidal turbine operations for the first time. By using these low computational techniques, it may be possible to address challenges such as underperformance due to the wake effects as well as forecasting, aiming to reduce uncertainty and enhance decision-making in operations and maintenance.